2019
DOI: 10.5935/1518-0557.20190009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus (HPV) in the semen of patients submitted to assisted reproductive technology treatment in a private clinic in Brazil

Abstract: Objective: The aim of our study was to identify the prevalence of HPV in the semen of men submitted to ART treatment and look into the possible impacts of the virus on sperm parameters. Methods: Thirty-five patients treated for infertility from March to August 2016 were invited to join the study. Samples with a minimum concentration of 40x10 6 spermatozoa per milliliter were included in the study. After the evaluation of semen parameters, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Also, there was a decrease in progressive motility (PR) and the normal morphology percentage in HPV‐positive samples (Yang et al., 2013). A study conducted by Bossi in Brazil between March and August 2016, HPV DNA was observed in 28% of specimens, and sperm motility was higher in HPV‐positive semen samples (Bossi et al., 2019). Fluorescence in situ hybridisation (FISH) analysis indicated that 25% of sperm samples had the DNA of HPV at the head site; however, the integration of HPV in the nucleus was not clear (Foresta et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Also, there was a decrease in progressive motility (PR) and the normal morphology percentage in HPV‐positive samples (Yang et al., 2013). A study conducted by Bossi in Brazil between March and August 2016, HPV DNA was observed in 28% of specimens, and sperm motility was higher in HPV‐positive semen samples (Bossi et al., 2019). Fluorescence in situ hybridisation (FISH) analysis indicated that 25% of sperm samples had the DNA of HPV at the head site; however, the integration of HPV in the nucleus was not clear (Foresta et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…76 Modern techniques like enzymatic clearance 5 and modified swim-up technique can eliminate HPV − DNA from infected sperm and improve the ART outcome. 77…”
Section: Assisted Reproductionmentioning
confidence: 99%
“…Therefore, in ART procedures, male partners infected with HPV seem to be a predictor of unsuccessful pregnancy results in 76 . Modern techniques like enzymatic clearance 5 and modified swim‐up technique can eliminate HPV − DNA from infected sperm and improve the ART outcome 77 …”
Section: Hpv‐dna Sperm Infectionmentioning
confidence: 99%